2013
DOI: 10.1074/jbc.m113.519637
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxycholesterol Activates the Integrated Stress Response to Reprogram Transcription and Translation in Macrophages

Abstract: Background:Interferons and viral infections stimulate the production of 25-hydroxycholesterol. Results: 25-Hydroxycholesterol significantly alters cholesterol ester and sphingolipid levels and activates the integrated stress response. Conclusion: 25-Hydroxycholesterol activates the GCN2/eIF2␣/ATF4 integrated stress response likely by causing cysteine depletion and/or by generating oxidative stress. Significance: Altering important membrane lipids and activating the integrated stress response may contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 67 publications
5
63
0
Order By: Relevance
“…Recent work by Shibata et al has demonstrated that 25HC can alter the transcriptional and translational program in macrophages by affecting the endoplasmic reticulum (ER) stress response (29). Our transcriptomic data are concordant with this study as we also detected increases in several stress response genes following stimulation of macrophages with 25HC, including Chac1, Trib3, Ddit3, Atf4, and Asns (GSE54064).…”
Section: Discussionsupporting
confidence: 81%
“…Recent work by Shibata et al has demonstrated that 25HC can alter the transcriptional and translational program in macrophages by affecting the endoplasmic reticulum (ER) stress response (29). Our transcriptomic data are concordant with this study as we also detected increases in several stress response genes following stimulation of macrophages with 25HC, including Chac1, Trib3, Ddit3, Atf4, and Asns (GSE54064).…”
Section: Discussionsupporting
confidence: 81%
“…Our results showed that 25HC could inhibit ZIKV infection in type I IFN signaling deficient A549 cells and in Ifnar −/− mice. However, 25HC may suppress ZIKV infection through other immune pathways, like activating integrated stress response (ISR) genes (Shibata et al, 2013) or the TLR4-dependent NF-kB pathway as described (Aye et al, 2012), which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we presume that activation of both the IRE1 and PERK arms is necessary for the induction of apoptosis. In this context, Shibata et al ( 53 ) have recently reported that 25-HC triggers integrated stress response via activation of GCN2/eIF2/ATF4 in macrophages. It would be intriguing to know whether the same pathway is activated in the Nceh1-dependent augmentation of 25-HC-induced ER stress, although it is beyond the scope of this study.…”
Section: Lipe Is Not Involved In 25-hc-induced Augmentation Of Macropmentioning
confidence: 99%